PENGARUH ASIMETRI INFORMASI, ESOP, KARAKTERISTIK PERUSAHAAN, DAN RASIO KEUANGAN TERHADAP MANAJEMEN LABA - Fanny Anggraeni; Sherly Noviyanti (E-Jurnal Akuntansi TSM, 2022)
This research was conducted with the purpose to obtain empirical evidence about the effect of information asymmetry, firm size, leverage, profitability, Employee Stock Ownership Program (ESOP), audit quality, and firm growth on earnings management. The research object used in this study are non-financial companies that listed in the Indonesia Stock Exchange (IDX) from 2017 to 2019. This research uses multiple regression analysis,and uses purposive sampling method for select the sample and obtain 588 samples studied. This research shows that the information asymmetry, firm size, leverage, and ESOP have no effect on earnings management. Whereas profitability, firm growth, and audit quality have an effect on earnings management.